The effects of kinesio tape on low back pain and disability in pregnant women - Tayebeh Aalishahi; Seyede Maryam-Lo; Zohreh Ghorashi; Ahmad Reza Sayadi (Wolters Kluwer Medknow Publications, 2022)
Background: Low Back Pain (LBP) is one of the most common complaints during pregnancy, which could cause performance disability. Kinesio tape is a drug-free elastic therapeutic cotton tape used in treating musculoskeletal problems. This study aims to determine the effects of Kinesio tape on LBP and disability in pregnant women. Materials and Methods: A total of 80 pregnant women with LBP who were referred to the comprehensive health service centers were randomly assigned into the two groups of Kinesio tape and adhesive tape. Pain intensity was determined by the visual analog scale before and on the 1st, 2nd, 7th, and 14th day after the intervention and the disability by Roland-Morris disability questionnaire before and on the 7th and 14th day after the intervention. Data analysis was performed by, Two-way repeated-measures ANOVA, Friedman, and Wilcoxon tests. Results: The intensity of pain decreased in both groups compared to the pre-intervention period; Kinesio (χ2 = 48.94, df = 4, p < 0.001) control (χ2 = 22.94, df = 4, p < 0.001); however, the comparison results of pain intensity were not different in the two groups at different times (p ≥ 0.05). The effects of time was significant (Two-way repeated-measures ANOVA, F1,83 = 10.63, p < 0.001), but the effects of time and group were not significant (F1,83 = 0.31, p = 0.722) and indicated a decreasing trend of functional disability in two groups. Conclusions: The Kinesio tape reduced the disability caused by LBP during pregnancy and had a lasting effect after the tape was removed.